2020
DOI: 10.7150/ijbs.44429
|View full text |Cite
|
Sign up to set email alerts
|

Septin4 promotes cell death in human colon cancer cells by interacting with BAX

Abstract: Septin4 is a tumor suppressor protein that promotes cell programmed death in various cell types through specifically antagonizing XIAP (X linked inhibitor of apoptosis), little is known its other novel binding partner and role in colorectal cancer. In this study, we found that Septin4 significantly expressed lower in human colon cancer when compared to peri-tumor benign cells, and its low expression was significantly associated with worse prognostic outcomes. Furthermore, Septin4 participated in DOX-induced co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…PLA2G4A [86], FGG (fibrinogen gamma chain) [87] and TYMS (thymidylatesynthetase) [88] have been demonstrated to be up regulated in cancer, but these genes might be liable for progression of PDAC. RAB32 [89], SEPTIN4 [90], TPM2 [91], ACOT7 [92], PRTFDC1 [93], CABLES1 [94], HLA-DMB [95], PTPRC (protein tyrosine phosphatase receptor type C) [96], CD5 [97], CD6 [97], MS4A1 [98], CD22 [99], CD27 [100], MRC2 [101], CLEC2D [102], EEF1A1 [103] and APOB (apolipoprotein B) [104] played a predominant role in the cancer progression, but these genes might be associated with development of PDAC. Jung et al [105] found that SMPD1 stimulates the drug resistance in colorectal cancer, but this gene might be linked with development of PDAC.…”
Section: Discussionmentioning
confidence: 99%
“…PLA2G4A [86], FGG (fibrinogen gamma chain) [87] and TYMS (thymidylatesynthetase) [88] have been demonstrated to be up regulated in cancer, but these genes might be liable for progression of PDAC. RAB32 [89], SEPTIN4 [90], TPM2 [91], ACOT7 [92], PRTFDC1 [93], CABLES1 [94], HLA-DMB [95], PTPRC (protein tyrosine phosphatase receptor type C) [96], CD5 [97], CD6 [97], MS4A1 [98], CD22 [99], CD27 [100], MRC2 [101], CLEC2D [102], EEF1A1 [103] and APOB (apolipoprotein B) [104] played a predominant role in the cancer progression, but these genes might be associated with development of PDAC. Jung et al [105] found that SMPD1 stimulates the drug resistance in colorectal cancer, but this gene might be linked with development of PDAC.…”
Section: Discussionmentioning
confidence: 99%
“…Septin4 is a protein localized at the mitochondrion that can promote cell death mainly by binding and inhibiting XIAP, thus activating caspases [74]. The interaction between XIAP and Septin4 has been implicated in several biological processes, such as apoptosis [75], cancer cell death [76], and neuronal differentiation [77]. In apoptosis, Septin4 enhances the binding between HIF-1α (hypoxia-inducible factor 1 alpha) and the E3 ubiquitin ligase VHL (von Hippel-Lindau protein) to down-regulate HIF-1α, which is a protective factor against hypoxia-induced apoptosis [75].…”
Section: Septin4 (-) Xiapmentioning
confidence: 99%
“…In cancer cell death, Septin4 translocates from the mitochondria to the cytoplasm and directly binds to XIAP, leading to caspase activation and cell death [76]. Septin4 also mediates the interaction between BCL2 (B-cell lymphoma 2) and XIAP, thereby positively regulating the ubiquitination and degradation of BCL2 and promoting apoptosis [78].…”
Section: Septin4 (-) Xiapmentioning
confidence: 99%
“…Septin 4 has also been reported to be a tumor suppressor that can promote the apoptosis of cancer cells. For example, Septin 4 could promote cell death in human colon cancer cells by increasing apoptosis ( 13 ). Another study revealed that silencing Septin 4 expression increased platelet-derived growth factor (PDGF)-BB-induced human aortic vascular smooth muscle cell (HAVSMC) proliferation, migration and phenotypic transformation, whilst the overexpression of Septin 4 had the opposite effects, implicating the involvement of Septin 4 in AS ( 14 ).…”
Section: Introductionmentioning
confidence: 99%